An in-depth study of the synthesis of ReSe2 for anisotropic Raman characteristics - Nam, Giho; Park, Sohyeon; Heo, Keun; Bong, Jungwoo; Lee, Dong Gyu; Kim, Hyunsoo; Ponnusamy, Krishna Moorthy; Bae, Hagyoul; Park, Hyeong Gi; Lee, Jae Hyun; Jang, Hyeon Sik (JPhys Materials, 2024)
Two-dimensional transition metal dichalcogenides (TMDs) have received more interest for their potential role in future electronic and optoelectronic applications. Unlike other TMDs, Rhenium diselenide (ReSe2) stands out for its distinctive anisotropic growth characteristics. These unique features arise from its low lattice symmetry and interlayer decoupling, this has sparked significant interest among researchers. Previous research has indicated the presence of various growth patterns, including dendritic formations and structures resembling flowers. In this study, we effectively produced ReSe2 using the ‘Tilting Boat’ method to achieve growth on a 21 μm scale. Through precise manipulation of the growth conditions, we successfully attained flakes of 21 μm scale in comparison to prior findings. Moreover, we successfully produced a variety of shapes, including triangles, diamonds, and hexagons, on 1 × 1 cm2 Si/SiO2 substrates. Furthermore, we achieved the successful production of a continuous ReSe2 film on a 1 × 3 cm2 Al2O3 substrate. We verified the distinct anisotropic properties of ReSe2 via Raman Spectroscopy. Furthermore, we acquired three-dimensional visual representations of ReSe2 flakes and continuous films via SEM measurements. By employing EDS data and analysing x-ray photoelectron spectroscopy spectra, we have established a compositional ratio of 1:2 for Re and Se, which aligns with the MX2 structure. This confirmation indicates the successful synthesis of high-quality ReSe2 flakes.
Keywords: Anisotropic; Chemical vapour deposition; Diselenides; Electronics applications; In-depth study; Optoelectronic applications; Raman characteristics; Tilted boat; Transition metal dichalcogenides (TMD); Two-dimensional; anisotropic; chemical vapor deposition; Raman spectroscopy; ReSe2; tilted boat